Penurunan Tingkat Depresi pada Pasien dengan Intervensi Minfulness Spiritual Islam - Asiah, Asiah; Dwidiyanti, Meidiana; Wijayanti, Diyan Yuli (Universitas Muhammadiyah Semarang, 2019)
Gangguan depresi salah satu masalah kejiwaan yang sering ditemukan, menyebabkan gangguan kualitas hidup yang berat hingga dapat membuat penderitanya melakukan percobaan bunuh diri.Intervensi mindfulness spiritual islam merupakan suatu latihan yang melibatkan Allah SWT dalam setiap proses dengan tujuan membantu individu untuk secara sadar memahami kondisi atau pengalaman yang dihadapi bukan sebagai kebetulan tetapi peristiwa dibuat oleh Allah SWT. Tujuan dari penelitian ini untuk menganalisis pengaruh mindfulness spiritual islam terhadap tingkat depresi pada pasien di RSJ. Quasi experimental with control group pre test -post testdesign. Populasi 195, purposive sampling dengan kriteria inklusi dan ekslusi, jumlah sampel 50 responden. Pengukuran tingkat depresi dengan BDI, Kelompok Intervensi menggunakan SOP mindfulness spiritual islam sebanyak 6 kali. Analisa bivariate menggunakan uji statistik Mann Witney U Test. Pada uji Mann-Whitney Test terdapat perbedaan tingkat depresi sesudah diberikan intervensi (p = 0,000 < 0,05), sehingga ada pengaruh intervensi Mindfulness dalam menurunkan tingkat depresi pada pasien diRSJ. Kata kunci: mindfulness spiritual islam, depresi REDUCE DEPRESSION LEVEL IN PATIENTS WITH ISLAMIC SPIRITUAL MINFULNESS INTERVENTION ABSTRACTDepressive disorder is one of the psychiatric problems that is often found, causing severe quality of life disorders that can make sufferers carry out suicide attempts. Islamic spiritual mindfulness interventions are exercises that involve Allah SWT in every process intending to help individuals to consciously understand the conditions or experiences encountered not as coincidences but events created by Allah SWT. The purpose of this study was to analyze the influence of Islamic spiritual mindfulness on the level of depression in patients at the Mental Hospital. Quasi-experimental with control group pre-post test design. Population 195, purposive sampling with inclusion and exclusion criteria, sample of 50 respondents. Measuring the level of depression using the BDI questionnaire, the Intervention Group used the Standard Operating Procedure of Islamic spiritual mindfulness 6 times. Research at Dr. Amino Gondohutomo Mental Hospital, Central Java Province in 2019. The results of the study were analyzed using the Mann-Whitney test, there were differences in the degree of depression after being given an intervention (p = 0,000 <0.05), there was an influence of the Mindfulness intervention in reducing the level of depression in patients at the Mental Hospital. Keywords: islamic spiritual mindfulness, depression